Trends in Cultural Tourism Research: A Bibliometric Analysis of Creative Economy Contributions - Judijanto, Loso; Suharto, Bambang; Pahrijal, Rival (Westscience Press, 2025)
This study explores trends and contributions in cultural tourism research within the context of the creative economy through a bibliometric analysis of publications indexed in Scopus. Using VOSviewer, the study identifies key themes, influential authors, and collaborative networks, revealing the central role of cultural tourism as a nexus for integrating cultural preservation, creativity, and economic growth. The analysis highlights sustainability, innovation, and digital transformation as emerging focal points in the field. Prominent researchers such as Greg Richards and theories like the experience economy are pivotal to the discourse, while international collaborations involving countries like Indonesia, the United States, and China demonstrate the global significance of cultural tourism research. Despite its growth, gaps in cross-regional representation, particularly in Africa and South America, highlight areas for future exploration. This study provides actionable insights for advancing cultural tourism strategies to align with sustainability goals and foster inclusive economic development.